Impact of stone bunds on temporal and spatial variability of soil physical properties: a field study from northern Ethiopia - Klik, Andreas; Schurz, Christoph; Strohmeier, Stefan; Demelash, Nigus; Ziadat, Feras M.; Schwen, Andreas; Zucca, Claudio (2018)
In the Ethiopian Highlands, stone bunds are a common practice for soil and water conservation, influencing runoff and erosion processes from sloped agricultural areas. The objective of this study was to investigate how stone bunds affect spatio-temporal relationships of these processes to better understand their impacts on soil water development at the smallholder farmer's field level. Study area was the Gumara-Maksegnit Watershed in Northern Ethiopia, where two representative transects were investigated: One transect crossed a 71 m long field intersected by two stone bunds (SB) traced along the contour. The second transect crossed a similar hillslope without conservation structures at a length of 55 m representing baseline (untreated) conditions (NSB). During the rainy season 2012, bulk density, volumetric water content were monitored as well as tension disc infiltrometer experiments were performed to determine the saturated hydraulic conductivity and to derive soil water retention characteristics. Our observations show that SB decreased significantly soil bulk density in center and lower zones of SB transect compared to NSB. No temporal change was observed. Results targeting the surface soil moisture indicate that infiltration was higher with SB and happened earlier in the rainy season in the zones around the SB. Saturated hydraulic conductivity was positively affected by SB and increased significantly. Improved soil hydrology by SB fields may increase crop yields by higher soil water contents but also by extending the growing season after the rainy season. Therefore, stone bunds are a successful measure to establish climate-resilient agriculture in the Ethiopian highlands.